Evolution of mechanical properties in a 7075 Al-alloy subject to natural ageing - Leacock, Alan G.; Howe, Conrad; Brown, Desmond; Lademo, Odd-Geir; Deering, Alan (Materials in engineering, 2013)
► Comprehensive mechanical test programme. ► 7075 Aluminium alloy solution heat treated and naturally aged up to 120min. ► Evolution of anisotropy following the solution heat treatment of 7075-O aluminium. ► Constant r-values and near linear increase in yield strength during natural ageing. ► Proposed semi empirical functions for interpolation of the experimental data set. A series of mechanical tests was used to characterise the evolution of yield strengths, r-values and work hardening during the natural ageing of a commercial 7075 aluminium alloy. The results show that there is a significant underlying change in anisotropy between the original O-condition and solution heat treated tempers. In the absence of recrystallisation, the abrupt change in anisotropy appears to have been caused by the modification of the precipitate during the solution heat treatment. The degree of induced anisotropy remained constant throughout the natural ageing process from 15 to 120min. A series of phenomenological functions is presented for the purpose of interpolation between the original test data points. These empirical functions are shown to predict the yield behaviour of the naturally aged material within the observed experimental scatter.